2019
DOI: 10.1007/s11904-019-00422-z
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Marijuana Use and HIV Continuum of Care Outcomes: a Systematic Review

Abstract: Purpose of Review Approximately 77% of HIV-infected adults report lifetime marijuana use. Given the high rates and social acceptability of marijuana use among HIV-infected individuals, it is important to gain a stronger understanding of if, and how, marijuana impacts HIV care cascade outcomes. The purpose of this study is to systematically review recent articles that assess the relationship between marijuana use and HIV continuum of care outcomes. Recent Findings One hundred and ninety articles from PubMed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…While some expressed concerns regarding the negative impact of RD, none made mention of concerns regarding the potential for RD to interact with their prescribed ART. With mounting evidence demonstrating that concurrent RD and ART may result in a range of negative consequences (20,28,32,35,36,38,40), initiatives to improve outcomes for PLHIV must address the unmet needs that drive them to engage in recreational drug use. For many, these needs are related to mental health issues, for which they appear to use RD to self-medicate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some expressed concerns regarding the negative impact of RD, none made mention of concerns regarding the potential for RD to interact with their prescribed ART. With mounting evidence demonstrating that concurrent RD and ART may result in a range of negative consequences (20,28,32,35,36,38,40), initiatives to improve outcomes for PLHIV must address the unmet needs that drive them to engage in recreational drug use. For many, these needs are related to mental health issues, for which they appear to use RD to self-medicate.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence confirms the wide-ranging negative impacts of non-adherence [40,[43][44][45][46][47][48]. Other studies have demonstrated that RD use is associated with poor social, mental and financial health [33,34,38,40,42]. CM are also known as 'traditional' or 'alternative' medicines and include substances such as vitamins, minerals, herbal remedies, aromatic oils and homeopathic products [49].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 2 studies that investigated symptom mitigation, one indicated an improvement [120] and one was inconclusive [115]. Among the 5 studies examining the effect of cannabis use on adherence to antiretroviral therapy, 2 indicated worsening [171,172], 2 reported no change [160,173], and 1 reported inconclusive findings [174]. One study examining the effect on viral suppression indicated no change [173], and 1 study indicated inconclusive findings [174].…”
Section: Human Immunodeficiency Virus/aidsmentioning
confidence: 99%
“…The lack of acknowledgment of these structural factors further masks other determinants of premature death impacting the low life expectancy of young Black males. Their troubling educational underachievement, poverty, unemployment, HIV/AIDS, cardiovascular disease, prediabetes, obesity, and smoking (e.g., cigarettes and marijuana) have been found to be factorial threats to their health and lead to premature deaths (Hazekamp et al, 2018; Jones-Eversley & Ravenell, 2018; Montgomery et al, 2019; Pathak, 2018).…”
Section: Peer-to-peer Homicidementioning
confidence: 99%